Assessing the Impact of Corporate Entrepreneurship in the Financial Performance of Subsidiaries of Colombian Business Groups: under Environmental Dynamism Moderation - Rodríguez Peña, Antonio (2021)
Corporate entrepreneurship creates opportunities in employment, technological advances, value creation and cultural transformation for entrepreneurial ecosystems, entrepreneurs, governments, economies and societies around the globe. The purpose of this study was to assess the impact of corporate entrepreneurship on the financial performance of subsidiaries in Colombian business groups under the moderating effect of the environmental dynamism, since the relationship between these two in emerging economies differs from developed economies. Using a cross-sectional Structural Equation Modeling analysis, this study assessed the impact of entrepreneurial orientation and corporate venturing on the financial performance of 87 subsidiaries of Colombian business groups at different levels of environmental dynamism. This study also confirmed that the relationship between corporate entrepreneurship and performance is context-dependent, and that entrepreneurial orientation has a strong and positive causal relationship with corporate venturing. Additionally, it was observed that subsidiaries of Colombian business groups increase their financial performance when the entrepreneurial orientation does; and decrease the same when corporate venturing does. Furthermore, the results show that environmental dynamism does not have a moderating effect on the relationship between corporate entrepreneurship of subsidiaries in Colombian business groups and their performance. This dissertation would contribute to important areas in Latin American businesses, where such studies are scarce.